Fatal elephant endotheliotropic herpesvirus-1 and -4 co-infection in a juvenile Asian elephant in Europe. Issue 2 (2nd April 2016) - Seilern-Moy, Katharina; Bertelsen, Mads F.; Leifsson, Pall S.; Perrin, Kathryn L.; Haycock, Jonathan; Dastjerdi, Akbar
Abstract : Introduction: Elephant endotheliotropic herpesvirus-1 (EEHV-1) is one of the major causes of fatality in juvenile Asian elephants ( Elephas maximus ). On occasions, other EEHV genotypes, i.e. EEHV-3, -4 and -5, have also been reported as the cause of Asian elephant deaths. In this case report we describe the investigation into a juvenile Asian elephant fatality in a European zoo. Case Presentation: A fatal case of haemorrhagic disease in a juvenile Asian elephant from a European zoo was diagnosed with co-infection of EEHV-1 and -4. EEHV-4 had a wider organ distribution and a higher viral load; both viruses presented the highest load in the mesenteric lymph nodes. Conclusion: Detection of EEHV-4 in this fatal case in Europe underlines the importance of inclusion of all known Asian EEHVs in routine blood monitoring to facilitate early therapeutic intervention.